OUTSOURCING CONTRACT AND ITS SPECIFIC SIGNS - Ямненко, Тетяна Михайлівна; Василенко, Вікторія Олегівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to define the term «outsourcing», to explore the concept of outsourcing contract and its attributes. Research methods: logical, formal-dogmatic, comparative-legal, etc. Results: definition of the term «outsourcing», the concept of outsourcing contract and its features based on these methods of research. Discussion: problems of legal regulation of outsourcing relations in Ukraine. Civil contract law contains many transactions that regulate a large number of civil relationships. Given that civil law is based on the principles of freedom of contract by civil law entities, it is quite coincidental that the appearance of new types of contracts and treaties, which include elements of already known civil law transactions that regulate commonly used legal relationships a new way, or even become a regulator of new contractual relationships. Such contracts should include an outsourcing contract. Outsourcing is the transfer from one company to another of some internal business processes for the purpose of their faster execution on a fixed term, for a certain price and with a certain level of services that a foreign company has to provide. In addition, outsourcing is also an enterprise management tool that includes the process of acquiring resources and services to improve the efficiency of the enterprise. It should be noted that the topic of legal regulation of outsourcing relations in Ukraine remains underdeveloped to date, even though there are a number of scientific articles concerning the definition of the concept of outsourcing contract and the nature of the origin of such contracts. The notion of outsourcing is closely related to the principles of contractuality and freedom of contract and, as a rule, scholars refer to this contract as mixed or unnamed contracts. It is also worth noting that although the outsourcing contract has not yet been isolated as a separate form, it already occupies an important place at the intersection of civil and commercial law, since it helps businesses regulate business relations in different markets for services and works. Thus, domestic civil and commercial law requires reform and a clear definition of the concept of outsourcing contract, as its use is becoming more popular and there is no legal support for its clear application.